Religious Moderation Campaign Through Social Media at Multicultural Communities - Anwar, Fatmawati; Haq, Islamul (LPPM IAIN Parepare, 2019)
Indonesia with its diversity of cultures, religions, ethnicities, languages ​​has established itself as a nation that has a multicultural society. This diversity becomes a blessing for Indonesia if it can be managed well. However, the reality of such plurality can also be a big challenge if it is not addressed wisely, it can even be a threat of division. This study aims to find out how religious moderation reinforces on social media. The research method uses a qualitative descriptive method by tracing the data related to the strengthening of religious mederation on social media. Social media has an important role in spreading and conveying religious messages in social and national life. Therefore the religious moderation campaign on social media needs to be developed in stemming the flow of religious discourse which lately tends to be exclusive and always blames others.